2019
DOI: 10.1002/chem.201901588
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Pd@M (M=Ni, Cu, Co) Nanoparticles/Graphene Ensembles with High Mass Electrocatalytic Activity Toward the Oxygen Reduction Reaction

Abstract: Herein, it is demonstrated that pyrene butyric acid (PBA)-stabilized metaln anoparticles with core-shell morphology, Pd@M NPs (M = Ni, Cu, Co), non-covalently supported on graphene (G) sheets, are more active towards oxygen electroreduction in alkaline environments than the benchmark Pd/C catalyst, albeit with a7 0% lower preciousm etal loading. The PBA-stabilized Pd@M NPs (M = Ni, Cu, Co)/G ensemblesw ere prepared by employing as imple modified polyol method andg alvanic replacementa nd thoroughly characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Many different functionalized nanostructures with different shapes have been described, including Janus nanoparticles, nanodendrites, alloys and core‐shell nanoparticles . Functionalization of PtNi alloys through simple adsorption of cyanides has a positive impact on the onset potential (E onset ) and half‐wave potential (E 1/2 ) of the catalyst compared to commercial Pt black, but especially enhances their methanol tolerance.…”
Section: Chemical Functionalization Of Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…Many different functionalized nanostructures with different shapes have been described, including Janus nanoparticles, nanodendrites, alloys and core‐shell nanoparticles . Functionalization of PtNi alloys through simple adsorption of cyanides has a positive impact on the onset potential (E onset ) and half‐wave potential (E 1/2 ) of the catalyst compared to commercial Pt black, but especially enhances their methanol tolerance.…”
Section: Chemical Functionalization Of Alloysmentioning
confidence: 99%
“…These nanocatalysts also show enhanced HER activity compared with PdNi catalysts without PEI. PdNi core‐shell nanoparticles stabilized by pyrenebutyric acid were deposited on graphene materials . These materials exhibit improved ORR performance in alkaline media compared to commercial Pd/C, with a 30 mV‐more positive E onset potential and a 3.2‐fold mass activity increase.…”
Section: Chemical Functionalization Of Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Without a doubt, the investigation and exploration of novel, less expensive, and abundant electrocatalysts for the ORR is of paramount importance. Recent research has focused on highly active catalysts driving the 4e − ORR, including Pt alloys [ 48 ], core-shell nanostructures [ 50 ], transition metal oxides [ 51 ], and chalcogenides [ 52 ], and carbon-based non-noble catalysts [ 53 , 54 ]. Carbon-based materials, such as graphene, doped graphene, and CNTs have been studied as conductive supports in ORR due to their excellent conductivity and high surface area [ 52 , 53 , 54 , 55 ].…”
Section: Cnhs In Electrocatalysismentioning
confidence: 99%
“…The composite strategy for bifunctionalo xygen electrocatalysis has been demonstrated to be effective in many cases. [46][47][48][49][50][51][52][53][54] For instance, Chen et al reported ac omposite of manganese dioxide andn itrogen-doped carbon nanotubes with high bifunctional electrocatalytic reactivity. [55] The composite of NiFe layered doubleh ydroxides with Co, Nc o-doped carbon nanoframesw as also provedt ob ee ffective for bifunctional oxygen electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%